KONTRIBUSI PEMANFAATAN PERPUSTAKAAN TERHADAP KELANCARAN PENULISAN SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN - 1725-1743 , Windha Sri Yuhartini (Universitas Negeri Padang, 2016)
ABSTRACTThis research is purposed to reveal the contribution of campus library toward script compiling for student of building engineering education study program at State University of Padang.This research was correlation with two variables. Sample collection technique was simple random sampling that amounted to 31 from 34 students of population.Data analysis technique consisted of: data descriptive, analysis requirement testing, hypothesis testing and coefficient determination testing. Research finding shows that there is a significant relationship between library utilization and script compiling of student with rcount value of (0.41 > 0.355) and level of confidence is 95%. Library utilization gives a contribution to students’ script compiling as many as 16.97% while the rest of 83.03% is caused by other factors. Keywords:contribution, script compiling, library utilization